The role and mechanism of bacterial outer membrane vesicles in the development of periodontitis - Wang, Haocheng; Sun, Jiale; Ma, Guoxuan; You, Fuping; Heng, Boon Chin; Bai, Yunyang; Deng, Xuliang (Frontiers in Microbiology, 2025)
Outer membrane vesicles (OMVs), nanoscale structures actively secreted by Gram-negative bacteria, have emerged as critical pathogenic components in periodontitis. While periodontitis has traditionally been associated with biofilm accumulation and bacterial colonization, recent studies highlight that OMVs contribute to disease progression independently of whole-cell bacterial presence. These vesicles are enriched with bioactive cargo such as lipopolysaccharides (LPS), proteases, DNA, and toxins, enabling them to persist in the periodontal microenvironment and interact with host immune and structural cells. They are also actively involved in biofilm formation and contribute to the development of antimicrobial resistance. Despite growing recognition of their involvement in periodontal disease, the extent of OMV interactions with host tissues and polymicrobial communities remains unclear. This review outlines the mechanisms through which OMVs influence inflammation, immune evasion, biofilm stability, and antibiotic resistance in periodontitis. It also highlights current knowledge gaps and concludes with potential therapeutic strategies targeting OMVs for the treatment of periodontitis.